The effect of walking speed on muscle function and mechanical energetics - Neptune, Richard R. (2007)
Modulating speed over a large range is important in walking, yet understanding how the neuromotor patterns adapt to the changing energetic demands of different speeds is not well understood. The purpose of this study was to identify functional and energetic adaptations in individual muscles in response to walking at faster steady-state speeds using muscle-actuated forward dynamics simulations. The simulation data were invariant with speed as to whether muscles contributed to trunk support, forward propulsion or leg swing. Trunk support (vertical acceleration) was provided primarily by the hip and knee extensors in early stance and the plantar flexors in late stance, while trunk propulsion (horizontal acceleration) was provided primarily by the soleus and rectus femoris in late stance, and these muscle contributions all systematically increased with speed. The results also highlighted the importance of initiating and controlling leg swing as there was a dramatic increase at the higher walking speeds in iliopsoas muscle work to accelerate the leg in pre- and early swing, and an increase in the biarticular hamstring muscle work to decelerate the leg in late swing. In addition, walking near self-selected speeds (1.2 m/s) improves the utilization of elastic energy storage and recovery in the uniarticular ankle plantar flexors and reduces negative fiber work, when compared to faster or slower speeds. These results provide important insight into the neuromotor mechanisms underlying speed regulation in walking and provide the foundation on which to investigate the influence of walking speed on various neuromotor measures of interest in pathological populations.